(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Acute appendicitis is one of the most common surgical emergencies. Accurate diagnosis of acute appendicitis is based on careful history, physical examination and laboratory and imaging findings. Objective: The primary aim is the correlation between clinical, biochemical and radiological assessment in patients of appendicitis and also to reduce the rates of negative appendicectomy. Method: The study was carried out in Department of General Surgery, Sir Sunderlal Hospital, IMS and BHU from September 2015 to July 2017. Total 61 patients of age group 16-65 years and either sex were evaluated on the basis of predetermined proforma, which included a detailed history, clinical examination, laboratory investigations and high resolution sonography or CT and histopathology. Sensitivities, specificities, positive and negative predictive values of TLC, neutrophil percentage, Modified Alvarado Score, CRP, D-dimer, USG and CT scan were calculated in respect to histopathology finding as a gold standard. Results: Modified Alvarado scoring (MAS 7-9:Appendicitis definitive) was present in 24 (39.3%) patients. Raised leucocyte count was present in 49 (80.32%) patients, while neutrophil count above 75% was present in 47 (77%) patients. Raised CRP was present in 55 (90.16%) patients with cut-off of >3 mg/l (normal range 1-3 mg/l) while D-dimer was elevated in 44 (72.13%) patients with cut-off of >5 mg/l. On ultrasonography,(77%) patients were diagnosed as acute appendicitis whereas (83.3%) had diagnosis of acute appendicitis in CECT abdomen. Histopathological examination was positive in 60 (98.4%) patients. Conclusion: We concluded that combination of thorough clinical evaluation along with certain routine biochemical & specific markers and ultrasonography as the primary imaging modality is sufficient in establishing a diagnosis of acute appendicitis in more than 90% cases.